Advances of natural hydrogel-based vascularization strategies for soft tissue repair - Xia, Zhuoheng; Guo, Bin; Wu, Danni; Yang, Fan; Ding, Yude (Frontiers in Materials, 2024)
Regeneration of soft tissues, especially those requiring complex vascularization, is a major challenge in the field of tissue engineering. The current types of tissue engineering scaffolds include sponges, electric spinning silk, hydrogels, and 3D printed biomaterials. Among them, hydrogels have the unique property of mimicking extracellular matrix (ECM), which can provide a relatively stable microenvironment for cellular activities and facilitate cell adhesion, proliferation, and differentiation; thus, have become a promising scaffold. In this paper, we present a review of the commonly used types of natural hydrogels and their applications as scaffolds in tissue vascularization. First, we enumerate the importance and advantages of several types of commonly used hydrogels of natural origin in terms of fabricating vascularized tissues or organs. Second, we discuss two different formation modalities of blood vessels, as well as natural hydrogel-based vascularization strategies, including carrying growth factors, stem cell delivery, special scaffold structures and pharmaceuticalenhanced strategy. In addition, we describe the crosslinking strategies of hydrogels as scaffolds for regeneration of vascularized soft tissues, as well as the factors affecting it. Finally, new insights are provided for the development of natural hydrogel-based vascularized soft tissue regeneration research.